Auditing - A.H. Millichamp (Cengage Learning EMEA, 2008)
This text provides a thorough and up-to-date coverage of auditing in a concise and readable style. It is widely used as a course text on professional accountancy and accounting degree courses. Numerous case studies, exercises, self testing questions and recent examination questions are included. This text is aimed predominantly at undergraduate and professional accountancy courses and the ninth edition prepared by John Taylor has been updated to take account of new International Auditing Standards